Comparison of Different Processing Methods of Iron Walnut Oils (Juglans sigillata): Lipid Yield, Lipid Compositions, Minor Components, and Antioxidant Capacity - Gao, Pan; Liu, Ruijie; Jin, Qingzhe; Wang, Xingguo (European journal of lipid science and technology, 2018)
A comparison study is performed on different processing methods of iron walnut oils (Juglans sigillata). Processing methods here include cold‐pressing (CP), roasting‐pressing (RP), n‐hexane extraction (HE), subcritical butane extraction (SBE), and supercritical carbon dioxide extraction. The lipid yield, physicochemical properties, lipid compositions, minor components, and antioxidant capacity of iron walnut oils are analyzed. Different processing methods do not affect the fatty acid compositions and triacylglycerol compositions of iron walnut oil. The lipid yields of pressing process (42.63–44.12%) is lower than that of the extraction process (48.13–63.44%). By multiple linear regression analysis, the results about the correlation between minor components and antioxidant capacity show that the RP process with high number of polyphenols (52.91 mg kg−1) indicates the highest antioxidant activity (DPPH: 574.73, FRAP: 111.80, ABTS: 498.53, ORAC: 523.34 µmol TE kg−1, respectively). Considering health and nutritional value of oil, RP can be a promising method for future iron walnut oil processing. Practical Applications: Iron walnut (Juglans sigillata) is a special walnut variety in China. In this study, five different processing methods of iron walnut oil are evaluated. The new iron walnut oil processing method is beneficial to the development of iron walnut oil. The authors show that lipid composition of tested oils is relatively stable, while their minor components contents are significantly different. Oil antioxidant capacity is mainly related to polyphenols. Roasting‐pressing can obviously improve the antioxidant activity of the iron walnut oil. This information has important directive to the nutritional value and industrial production of iron walnut oil. Iron walnut oil is obtained from Juglans sigillata by different processing methods, including cold‐pressing, roasting‐pressing, n‐hexane extraction, subcritical butane extraction, and supercritical carbon dioxide extraction. The lipid yield, physicochemical properties, lipid compositions, minor components, and antioxidant capacity (DPPH, FRAP, ABTS, and ORAC) are analyzed. Models deduced by multiple linear regression are recognized as acceptable for predicting the antioxidant capacity of the iron walnut oil. Iron walnut oil is obtained from Juglans sigillata by different processing methods, including cold‐pressing, roasting‐pressing, n‐hexane extraction, subcritical butane extraction, and supercritical carbon dioxide extraction. The lipid yield, physicochemical properties, lipid compositions, minor components, and antioxidant capacity (DPPH, FRAP, ABTS, and ORAC) are analyzed. Models deduced by multiple linear regression are recognized as acceptable for predicting the antioxidant capacity of the iron walnut oil.